Remote variants of the disappearing lung syndrome as a complication of COVID-19 pneumonia - М.І. Lynnyk; М.І. Gumeniuk; O.K. Yakovenko; V.І. Іgnatieva; G.L. Gumeniuk; V.А. Svyatnenko (Civic Union "Communicable Diseases Intensive Care Association", 2023)
BACKGROUND. The pandemic of the coronavirus disease (COVID-19) associated with the SARS-CoV-2 virus has left many complications, including the pulmonary system. One of them is the syndrome of disappearing lungs. It occurred both in the acute period of the disease and in the post-COVID period (after 3-4 months) after inpatient treatment. Remote variants of the disappearing lung syndrome as a complication of COVID-19 pneumonia have not been studied to date. OBJECTIVE. To study distant variants of the course of the disappearing lung syndrome as one of the complications of nosocomial pneumonia of viral etiology (COVID-19) and to demonstrate it on clinical observations. MATERIALS AND METHODS. The dynamics of computed tomography (CT) data of patients with a complicated course of nosocomial viral pneumonia (COVID-19), who were treated at the SI "National Institute of Phthisiology and Pulmonology named after F.G. Yanovsky of the NAMS of Ukraine". RESULTS. Remote variants of the course of the disappearing lung syndrome as a complication of COVID-19 pneumonia are the development of bullous or diffuse emphysema of the lungs, giant thin-walled cyst-like cavities, and recurrent pneumothorax and pneumomediastinum. These variants are very diverse, and their results can be different even with identical radiological manifestations. CONCLUSIONS. The most unfavorable variant of the course of the disappearing lung syndrome is the development of recurrent pneumothorax and pneumomediastinum, which requires observation for more than 1.5-2 years and control CT scans of the chest.